Two new species of Trimma (Pisces; Gobiidae) from Fiji, south-western Pacific Ocean - Winterbottom, Richard (Zootaxa, 2017)
Two new species of Trimma are described from Fiji. Trimma bathum n. sp. lacks scales on the cheeks, opercle and predorsal midline, has 18–19 unbranched pectoral fin rays, an unbranched 5th pelvic fin ray that is 40–56% the length of the 4th ray, 17–18 gill rakers on the outer surface of the first gill arch, a U-shaped interorbital and a narrow slit-like postorbital trench, a low, median fleshy ridge extending half-way towards the orbit from the origin of the first dorsal fin, and, when freshly collected, a pink head and body with most body scales having an orange-brown spot or short bar at their centres. The species is currently known only from off Suva Harbour, Viti Levu, Fiji. Trimma finistrinum n. sp. has a bony interorbital equal to the pupil diameter, a fully scaled nape of 12–14 scales, a second dorsal spine that may reach posteriorly to the middle of the second dorsal fin, the papillae in the longitudinal row immediately below the eye either single or with two papillae in a vertical row, unbranched pectoral fin rays, usually a branched fifth pelvic-fin ray that is about half length of the fourth ray, and a large diffuse dark blotch on the posterior part of the caudal peduncle. A colour pattern of a brownish body with most body scales having golden- to greenish-yellow (pale in preservative) centres is unique among species of the genus. The species is currently recorded only from off the north and east coasts of Viti Levu, Fiji.